Havana Thursdays : a novel - Suárez, Virgil, 1962- (Arte Público Press, 2017)
The impact of death on a family. The deceased is Zacarias Torres, a Miami botanist who suffers a heart attack while in Brazil. As the family gathers for the funeral, grievances and frustrations are aired, consciences are examined and it's all for the better. By the author of Welcome to the Oasis.